An accurate estimation of the horizontal acceleration of a rower`s centre of mass using inertial sensors: a validation - Lintmeijer, L. L.; Faber, G. S.; Kruk, H. R.; Knoek van Soest, A. J.; Hofmijster, M. J. (European Journal of Sport Science, 2018)
For a valid determination of a rower`s mechanical power output, the anterior-posterior (AP) acceleration of a rower`s centre of mass (CoM) is required. The current study was designed to evaluate the accuracy of the determination of this acceleration using a full-body inertial measurement units (IMUs) suit in combination with a mass distribution model. Three methods were evaluated. In the first two methods, IMU data were combined with either a subject-specific mass distribution or a standard mass distribution model for athletes. In the third method, a rower`s AP CoM acceleration was estimated using a single IMU placed at the pelvis.